Dualism in the South Halmahera Government’s Policy on Managing Diversity in the Bacan Sultanate - Flavius Floris Andries (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
The issue of dualism in the South Halmahera government policy on managing cultural diversity in the Bacan Sultanate is an interesting phenomenon to study. Saruma, the multicultural icon used to manage diversity in the Bacan Sultanate, is not reflected in governmental policy or society, in general. This study focused on three research questions: 1) What is the socio-historical context of the Bacan Sultanate from which the concept of Saruma emerged? 2) Why has the South Halmahera government failed to apply the concept of Saruma in its policy on managing diversity? 3) What are the impacts of this dualism on the people? This qualitative research employed observation techniques to understand the community’s dynamics. In-depth interviews were conducted to obtain data concerning the people’s social lives as well as the government’s policy and its impact on society. A literature review was undertaken to understand related research and to formulate a theoretical framework as an analytical device. The results showed that in spite of the cultural authority owned by the Sultanate, the absence of political authority has led to a failure to implement its Saruma concept in managing the cultural diversity. The change of political system from representation to participation has also led to transactional politics, which benefits the majority but disadvantages the minority, and the traditions of domination and hegemony, in turn, have discriminated against the minority, endangering their identity.